Targeting farmers in institutional procurement programmes: Case study of the PAA Africa Programme in Senegal - Rosana Pereira de Miranda; Abdoulaye Thiam; Israel Klug (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
Like other Sahel countries, Senegal experienced a succession of food and nutrition crises in 2005, 2008, 2010 and 2012. In 2012, severe food insecurity affected around 739,000 people, corresponding to 6.2 per cent of the Senegalese population. Nutrition surveys conducted in 2012 showed overall acute malnutrition rates ranging from 10 to 15 per cent, with 16 of the country's 45 départements reaching the alert threshold. Moreover, severe acute malnutrition rates ranging from 2 to 4 per cent were recorded in eight départements and consequently regarded as a crisis phase (WFP 2011).
Keywords: 330; Targeting; farmers; institutional; procurement; programmes; case; study; PAA Africa; Programme; Senegal